INVESTIGATING ENGLISH TEACHING PROCESS TROUGH COMMUNICATIVE LANGUAGE TEACHING APPROACH TOWARDS STUDENTS’ SPEAKING SKILL - Lestari, Novi Puji (JELLE, 2024)
This research aimed to investigate English teaching process through Communicative Language Teaching approach (CLT) towards students’ speaking skill. This research used a descriptive qualitative approach. The researcher used observation to get the primary data and interview as the secondary data. The researcher obtained the data from the observation of classroom activity at the one of English course located in Cilegon named ENTER English Center. Moreover, the researcher conducted an interview with one teacher and two students from one of the classrooms in ENTER. From the investigation, the researcher found that communicative language teaching is an effective approach towards students’ speaking skill. The various interactive classroom activities improve students’ enthusiasm in learning. Furthermore, the researcher found that communicative language teaching successfully helps students in improving fluency and confidence in speaking as oral communication. In other words, communicative